When nationalism meets hip-hop: aestheticized politics of ideotainment in China - Zou, Sheng (Communication and critical/cultural studies, 2019)
This essay unravels the coalescence between bottom-up youth culture and state-led ideological work in China by examining the patriotic hip-hop music videos of a Chinese youth band. I attend to the ways in which the state-centric ideology is aesthetically evoked by co-opting popular cultural formats, maneuvering grassroots nationalistic expressions and appropriating symbols of both tradition and modernity. Hip-hop is thus localized and sanitized as a cultural medium of propaganda. The limitations of such co-optative tactics are also discussed, particularly the tradeoff between ideological control and authentic expressivity, and the risk of de-sublimating auratic cultural symbols for political persuasion.